The association between the duration of surgery and risks of mortality and unplanned reoperation is modulated by the surgical start time - Zilong Mao; Jinan Zhang; Peng Wang; Wei Zuo (Scientific Reports)
Abstract To evaluate the associations of neurosurgical start and duration with surgical outcomes. This retrospective study analysed elective neurosurgery data from January 1, 2017, to December 30, 2021. Unplanned reoperation and postoperative mortality during hospitalization were the outcomes. We divided the surgical start time, duration and completion time into categories (Q1: 8–13:00; Q2:13–17:00; and Q3: others), (Q1: less than 5 h; Q2: 5–10 h; and Q3: others), and (Q1: 08–18:00; and Q2: others). Generalized linear mixed models were used to explore associations between surgical time subgroups and outcomes. Interaction analyses were performed to evaluate surgical outcomes and subgroup interaction associations. In total, 16,549 patients were analysed, and 611 patients had adverse outcomes. Compared with earlier start times and shorter durations, later start times and longer durations were associated with 200 and 600% greater risks, respectively. Compared with earlier and longer-duration surgeries, earlier and longer-duration surgeries were associated with a lower risk of adverse events. These data indicate that a later surgical time and longer duration are associated with more adverse surgical results. Furthermore, the association between the duration of the operation and surgical outcomes might be modulated by the surgical start time.